The effect of ground oyster mushroom (pleurotus sajor- caju) in the nutritional enhancement, physicochemical properties and structural changes of herbal seasoning - Sa'ari, Saiful Bahri (2015)
Globally, human of different ethnicities have known mushroom for long time ago. The mushrooms have been used as normal diet since they are recognized as a delicacy and possess unique taste and odour (Mattila et al., 2000). Mushrooms are grouped in the Fungi Kingdom. In the past, they were categorized as plants. Mushrooms belong to the class of Basidiomycetes and order Agaricales. They do not have the ability to synthesize foods like green plants and these special types of edible fungi forming flesh umbrella like fruiting bodies (Bahl, 1998). Mushrooms are different in sizes, colours, textures and structures that favour their spore formation. The cap is known as cuticle and normally varies among different mushroom species and texture is sticky or slimy. The stalk is the stem-like structure on which the cap is mounted and the length is varies depending on the species (Gyar and Ogbonna, 2006).